2023
DOI: 10.3390/biomedicines11061573
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Metabolism: An Emerging Therapeutic Target to Improve CKD Outcomes

Kranti A. Mapuskar,
Gabriela Vasquez-Martinez,
Gabriel Mayoral-Andrade
et al.

Abstract: Chronic kidney disease (CKD) predisposes one toward end-stage renal disease (ESRD) and its associated morbidity and mortality. Significant metabolic perturbations in conjunction with alterations in redox status during CKD may induce increased production of reactive oxygen species (ROS), including superoxide (O2−) and hydrogen peroxide (H2O2). Increased O2− and H2O2 may contribute to the overall progression of renal injury as well as catalyze the onset of comorbidities. In this review, we discuss the role of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…These lipid classes play diverse and intricate roles in kidney mitochondria, participating in key cellular processes. TGOs and TGs serve as energy substrates and act as a storage form of fatty acids in kidney mitochondria 123,124 . Disruptions to these lipids can impact mitochondrial beta-oxidation, providing acetyl-CoA for energy production.…”
Section: Discussionmentioning
confidence: 99%
“…These lipid classes play diverse and intricate roles in kidney mitochondria, participating in key cellular processes. TGOs and TGs serve as energy substrates and act as a storage form of fatty acids in kidney mitochondria 123,124 . Disruptions to these lipids can impact mitochondrial beta-oxidation, providing acetyl-CoA for energy production.…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the life protection mechanism of Bact A or Bact B, we focused on the roles of intracellular antioxidant pathways. It has been reported that many antioxidants could demonstrate efficacy in reducing the severity of AKI and delay the progression of several kidney diseases [ 29 ]. In line with this, the result of Western blotting shows that the protein expression of Nrf2 and/or Ho-1, which are eminent molecules capable of being involved in the antioxidants pathway, were more or less high in the Cis/Bact A and Cis/Bact B group mice rather than that in the Cis group mice ( Figure 6 A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular cells, including podocytes, endothelial cells, and mesangial cells, mainly function to filter blood under the glomerular filtration pressure [16]. This passive process does not consume ATP, and ATP is primarily used to maintain cellular homeostasis.…”
Section: Selection Of Energy Substratesmentioning
confidence: 99%